Comparison of the Formulation, Stability and Biological Effects of Hydrophilic Extracts from Black Elder Flowers (Sambucus nigra L.) - Aurelijus Laurutis; Julius Liobikas; Monika Stanciauskaite; Mindaugas Marksa; Kristina Ramanauskiene; Daiva Majiene (MDPI AG, 2022)
Elderflower preparations have long been used to treat colds and flu, but their use is undeservedly reduced, and only dried flower teas, less often ethanolic extracts, can be purchased in pharmacies. In the case of homemade teas, the medicinal plant material is extracted with hot water for a relatively short time, thus only a small part of the active substances is extracted. The industrially produced ethanolic extract is rich in active substances, but its use is limited since ethanol in many countries is undesirable and unsuitable for children and geriatric patients. Therefore, the aim of this work was to produce extracts from elder flowers using water as extractant and a mixture of water + polyethylene glycol (PEG) 20%, to compare their chemical composition and stability, and to study the ability to neutralize reactive oxygen species (ROS) and to sustain the viability of C6 glial cells under oxidative stress conditions. The ethanolic extract was used as a standard. Thus, the extract with PEG contained more than two times higher amount of total phenolics (PC) than the aqueous one, and the stability at 6-8 °C was comparable to the stability of ethanolic extract. All three extracts showed an antioxidant effect in a concentration-dependent manner in vitro. However, only the PEG containing extract (at 20-40 µg/mL PC) was the most effective in reducing the intracellular level of ROS and sustaining the viability of glial cells. The results suggest that the co-solvent PEG increases the yield of phenolics in the extract, prolongs the stability, and enhances positive biological effects.